Pengembangan Sistem Informasi Pengelolaan Jadwal dan Ruangan berbasis Website - Adhitya Pratama, Yudhistira; Pratama, Yudhistira Adhitya; Nababan, Adli Abdillah; Maulana, Ade; Dulianto, Des; Harefa, Ade May Luky (CV. ADMITECH SOLUTIONS, 2024)
The rapid development of information technology has significantly impacted various aspects of life, including management and administration. Efficient scheduling and room management remain a major challenge for educational, governmental, and private institutions. Manual processes are often time-consuming, prone to errors, and lack flexibility in responding to dynamic changes. This research aims to design and develop a web-based information system for scheduling and room management to address these challenges effectively. The system provides features such as building and room management, schedule management, and user account handling, enhancing accessibility and reducing overlapping schedules and allocation errors. The development process involves system requirement analysis and modeling using Use Case and Entity Relationship Diagrams. The resulting system simplifies real-time monitoring, automates manual processes, and improves institutional operational efficiency. Testing through black-box methods confirmed the system's functionality and user-friendliness, ensuring reliable implementation for users. This study contributes to technological advancement by offering a practical solution to operational inefficiencies while laying the groundwork for further enhancements in system functionality and user interface design.